Kinerja Musrenbang Provinsi Lampung 2017 - Dedy Hermawan; Ridwan Saifuddin; Sigit Prasetyo (Balitbangda Provinsi Lampung, 2018)
Musrenbang is the first step of the development process which is expected to be born in harmony of direction and priority of the program, so that the central and regional development process is synergy and integrated. This study identifies and compares the national priorities program and Lampung Province, as stated in the Government Work Plan (RKP) and Regional Government Work Plan (RKPD) of Lampung Province 2017. Also, the national medium-term planning document (RPJMN) and Lampung Province (RPJMD) 2015-2019. The results of identification, from 88 indicators related to the target area, there are 79 indicators that have been realized Lampung Province, or in other words, the level of suitability of the program of 88.76%, which according to Performance Rating Scale of the Ministry of Internal Affairs, included in the category of high .